2019
DOI: 10.1126/science.aav3200
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic decarboxylative alkylations mediated by triphenylphosphine and sodium iodide

Abstract: Most photoredox catalysts in current use are precious metal complexes or synthetically elaborate organic dyes, the cost of which can impede their application for large-scale industrial processes. We found that a combination of triphenylphosphine and sodium iodide under 456-nanometer irradiation by blue light–emitting diodes can catalyze the alkylation of silyl enol ethers by decarboxylative coupling with redox-active esters in the absence of transition metals. Deaminative alkylation using Katritzky’s N-alkylpy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
325
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 599 publications
(358 citation statements)
references
References 65 publications
7
325
0
4
Order By: Relevance
“…[9] Recent studies revealed that RAEs could be efficiently activated through formation of electron-donor-acceptor complex with an electron donor species under irradiation. [10] The electron-donor-acceptor complex can be a transient encounter complex, which is formed in equilibrium in solution through weak non-covalent interactions, [11] such as Coulombic interaction, hydrogen bonding, and π-π stacking, which are heavily affected by solvation. With our interest in development of inexpensive methodologies to use aliphatic carboxylic acids in organic synthesis, [12] we conceived that decarboxylative conjugated addition with Michael acceptors and hydrodecarboxylation could be performed with a electron donor substrate such as Hantzsch ester (HE) under mild irradiation condition using blue LEDs.…”
mentioning
confidence: 99%
“…[9] Recent studies revealed that RAEs could be efficiently activated through formation of electron-donor-acceptor complex with an electron donor species under irradiation. [10] The electron-donor-acceptor complex can be a transient encounter complex, which is formed in equilibrium in solution through weak non-covalent interactions, [11] such as Coulombic interaction, hydrogen bonding, and π-π stacking, which are heavily affected by solvation. With our interest in development of inexpensive methodologies to use aliphatic carboxylic acids in organic synthesis, [12] we conceived that decarboxylative conjugated addition with Michael acceptors and hydrodecarboxylation could be performed with a electron donor substrate such as Hantzsch ester (HE) under mild irradiation condition using blue LEDs.…”
mentioning
confidence: 99%
“…[28] Recently,Fu, Shang, and their co-workers have discovered that in cooperation with triphenylphosphine,N aI can initiate aw ide range of radical reactions promoted by blue light. [29] Scheme 5. Photo-promoted couplings of aryl triflates with type-III nucleophiles.…”
Section: Càib Ond Formation:r Eaction With Sodium Iodidementioning
confidence: 99%
“…[8] In recent years, alkyl N-hydroxyphthalimide (NHP) esters was emerged as an efficient decarboxylation alkylation reagent because it could be reduced by photocatalyst,g enerating av ariety of alkyl radicals via elimination of CO 2 and phthalimide. [9] For example, the regioselectivea lkylation of N-heteroarenes with alkyl NHP esters under irradiation of blue LEDs was achieved by Shang and Fu. [10] We supposed that this process also could be applied for the synthesisof3-alkylated quinoxalin-2(1H)-ones.W ith our ongoing interesto n developing green and efficient methods for direct CÀHf unctionalization, [11] herein, we report am etal and oxidant free Minisci type reactiono fq uinoxalin-2(1 H)one with alkyl NHP esters via ap hotocatalytic system promoted by visible light, leading to the synthesis of av ariety of 3-alkylated quinoxaline-2(1H)ones in moderate to excellent yields.…”
Section: Introductionmentioning
confidence: 99%